THE EFFECTvOF THE USE OF VIDEO TUTORIALS ON LEARNING INTERESTS AND SCIENCE LEARNINGvOUTCOMES OF GRADEvVIII A STUDENTSvOF SMP MUHAMMADIYAH 10 MUNCAR - Imron Rosadi Mohammad (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2022)
The Covid-19 pandemic has had a major impact on various sectors, one of which is education. The world of education is also feeling the impact. In the past, before the Covid system and learning models were carried out face-to-face between teachers and students, the problem in this study was whether video tutorial-based learning media could affect science learning outcomes. The respondents of this research were class VIII students of SMP Muhammadiyah 10 Muncar with a total of 30 students. This research was a quantitative study with a causal design. Valid and reliable degree with validity and reliability tests. Instrument analysis test using: 1) Descriptive test, 2) Normality test 3) Homogeneity test. Test the hypothesis using: 1) Regression analysis, 2) F test, 3) T test The results show that: 1) sig. from the learning video tutorial variable, there is a motivation of 0.000, so the conclusion is sig > 0.05, meaning that there is an influence of video-tutorial-based learning media on students' interest in learning science. 2) the sig value of the influence variable of video tutorial-based learning media on learning outcomes is 0.000. The conclusion obtained is sig > 0.05, it means that there is an influence of video tutorial-based learning media on students' natural science learning outcomes. 3) the output results of the regression analysis obtained F count 29.124 with sig 0.000, because > 0.05, there is an influence of video tutorial-based learning media on learning interest and science learning outcomes in students, especially junior high school students.